Strategy for Combating the Crime of Sap Theft at PT Bridgestone: Juridical Analysis of Decision Number 590/Pid.B/2019/PN.Sim - Azhari Rais; Sarles Gultom; Elpina Elpina; Parlin Dony Sipayung; Josua Situmeang (Journal Analytica Islamica, 2023)
The theft of sap that occurs is very disturbing to the security and order of the community. The crime of sap theft is a problem that is very detrimental to many parties, including plantation owners. Theft is the most common type of crime in the midst of community life. Although this crime is not a crime classified as a serious crime, it can cause unrest in the community. so that legal efforts are needed by the police in tackling the crime of sap theft which is increasingly rampant. The purpose of this research is to find out the factors of the occurrence of the crime of theft of sap by the community, the legal regulation of the crime of theft of sap, and to find out the efforts to overcome the law apparatus in the theft of sap committed by the community. The type of research used is empirical juridical research, which is descriptive in nature, which uses data collection tools in the form of interview techniques and literature studies, and is continued by conducting qualitative analysis. The factor that is most often used as an excuse for the perpetrators of the crime of sap theft is economic factors, accompanied by environmental factors and the low level of education of the perpetrators. The crime of theft of sap is basically regulated in Article 362 of the Criminal Code and the crime of petty theft is regulated in Article 364 of the Criminal Code which is adjusted based on Supreme Court Regulation Number 2 of 2012 concerning Adjustment of the Limitation of Petty Crimes and the Amount of Fines in the Criminal Code. The countermeasures taken by the Police by taking preventive actions by conducting counseling and routine patrols, while repressive actions are in the form of arrests, investigations, investigations and so on against the perpetrators. The solution of this research is that law enforcers should further increase countermeasures with the earliest possible prevention of the crime of sap theft.